Motivational Factors of Social Media Influencers : The context of travel influencers - Tähtinen, Sanni (My University, 2020)
This study researches work motivation among social media influencers, more precisely, travel influencers who are entrepreneurs and represent Generation Y. Further, the study considers how organizations could attract travel influencers to join them as employees instead. The importance of social media as a part of organizations’ marketing strategies is increasing. Therefore, organizations need expertise among social media. Lately, the phenomenon of influencer marketing has aroused meaning that people with a substantial number of followers on social media are promoting organizations’ products on their channels and this way influencing consumers’ purchasing decisions. As social media influencers have the expertise among social media, they are a suitable source of workforce for organizations in need of social media skills. Therefore, it is valuable to understand work motivation among social media influencers to be able to attract them to work for organizations. Also, understanding social media influencers’ work motivation is beneficial to organizations collaborating with them. To achieve a thorough understanding of the phenomenon, a comprehensive literature review among motivation, entrepreneurship, Generation Y and social media is conducted. Basing on the literature review, theoretical framework as well as propositions for the empirical research are formulated. The research is conducted through an extensive case study and the data is collected through semi-structured interviews among five travel influencers. The findings indicate that travel influencers’ motivational factors for work can be explained through their needs, intrinsic and extrinsic motivational factors, their goals and their self-efficacy towards work. Basing on the interviews, travel influencers’ needs can be categorized on the levels of safety, love, esteem and self-actualization. Further, travel influencers seem to be mostly motivated either by the need for affiliation or the need for achievement, or both. The nature of travel influencers’ motivational factors seems to be rather intrinsic. However, extrinsic factors seem to support the intrinsic factors. When it comes to setting goals, travel influencers do not seem to be motivated by consciously set targets. However, it seems that travel influencers’ actions are commonly guided by their values as they are willing to work in line with them. Also, the findings indicate that travel influencers increase their work motivation by strengthening their self-efficacy. This study contributes to the previous literature among social media influencers by offering a broad overview on the factors that motivate travel influencers in their work. It also considers aspects that travel influencers find attractive and unattractive in organizational work, which is helpful for organizations in need of expertise among social media and willing to recruit social media influencers or collaborate with them. All in all, this study complements the prior research among work motivation of social media influencers, especially travel influencers.
Keywords: Work motivation; Entrepreneurship; Generation Y; Social media influencer; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business